Violence and collective trauma through ‘Night’ in contemporary Acehnese novels - Ritonga, Mhd Rasid; Pratiwi, Siti Habsari; Suhery, Dedy; Nadrah, Nadrah (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
The long-lasting conflict between the Indonesian administration and GAM ended in 2004. Yet, while the fighting came to an end, the residue and fragments of the conflict remained. The attempt to reconcile with violence and trauma is best captured through the works of contemporary Acehnese writers. Among other works of fiction, the novel writers try to express what the conflict meant for the Acehnese people. To this end, the current article is aimed at exploring Acehnese representations of violence and trauma through the metaphorical and symbolic meaning of ‘night’ in five contemporary Acehnese novels. This paper demonstrates the way the Acehnese contemporary writers represent the violence and trauma through the metaphor of ‘night’. Qualitative content analysis was used to reduce, narrow, and categorize the words, phrases, or paragraphs extracted from the novels. The data was analyzed by a post-conflict approach. The novels reveal kinds of violence and trauma through the imagery of ‘night’ highlighting multi-layered experiences during the conflict and bring the concept of postcoloniality through their writing. The five novels have tried to bring into play the ‘unfinished business’ of post-conflict Aceh. The novels also highlight the role of contemporary Acehnese novels in post-conflict societies. The disappeared left buried or unburied, the violence, the unresolved trauma, the continuing inequalities and injustices, and the struggle during the conflict means that the Aceh of the past haunts and disturbs the Aceh of the present.